2017
DOI: 10.1155/2017/1832853
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effect of Dialyzable Leukocyte Extract in Autoimmune Prostatitis: Evaluation in Animal Model

Abstract: Objective. To evaluate the anti-inflammatory properties of Dialyzable Leukocyte Extract (DLE) in a murine model of chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS). Methods. Histopathological characterization, prostatein Enzyme-Linked Immunosorbent Assay, and immunohistochemical analysis for CD45, TNF-α, IFN-γ, IL-6, IL-17, and IL-4 molecules were done in prostatic Wistar rats treated with DLE, placebo, or Dexamethasone. Results. Histopathological analysis of animals induced to prostatitis showed inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
(63 reference statements)
0
4
0
2
Order By: Relevance
“…IFN-γ has been widely recognized as a signature pro-inflammatory cytokine that plays a central role in inflammation, and several studies have suggested a crucial role for IFN-γ in the pathogenesis of experimental prostatitis in animal models 2728. Thus, we have evaluated the serum concentration of the pro-inflammatory cytokine in our carrageenan-induced prostatitis model.…”
Section: Resultsmentioning
confidence: 99%
“…IFN-γ has been widely recognized as a signature pro-inflammatory cytokine that plays a central role in inflammation, and several studies have suggested a crucial role for IFN-γ in the pathogenesis of experimental prostatitis in animal models 2728. Thus, we have evaluated the serum concentration of the pro-inflammatory cytokine in our carrageenan-induced prostatitis model.…”
Section: Resultsmentioning
confidence: 99%
“…Decrease of inflammatory infiltrates, morphological changes to similar of normal prostate, and prostatein decreased to basal levels was reported in DLE group with decreased CD45 expression and proinflammatory cytokines TNF-α, IFN-γ, IL-6, IL-17. In summary: DLE is able to modulate inflammatory response in experimental autoimmune prostatitis [24].…”
Section: Results -Immunologic and Clinical Responsementioning
confidence: 94%
“…En un modelo murino de prostatitis crónica/ síndrome de dolor pélvico, se demostró que el tratamiento con EDLc produce una disminución de la expresión del marcador de la superficie CD45 y de las citocinas proinflamatorias TNF-a, INF-y, IL-6 e IL-7, con lo cual se demuestra la modulación los efectos patológicos de la prostatitis autoinmune experimental (Pérez-Alvarado et al, 2017).…”
Section: Actividad Anticancerígenaunclassified